(untitled) - Smith, Chuck; 1927- (U.S.A., 1994)
In this deeply relational book, noted Bible teacher Chuck Smith explores 12 great themes of God's unending, beautiful grace. With the passion of a man whose own life has been transformed by this gift, Smith clearly explains why: We are not bound to God by a huge list of do's and dont's
English
Keywords: Grace (Theology)